Digitalisasi UMKM Berbasis Potensi Lokal dalam Upaya Pengentasan Kemiskinan Di Era Efisiensi Multi-Level Government - Iman Teguh; Amir Hamzah; Oktaviani Rita Puspasari (JAMARI : Jurnal Pengabdian Masyarakat Mandiri, 2026)
This Community Service was carried out in Karoya Village, Cipicung District, Kuningan Regency, in response to the high levels of poverty and open unemployment in the region, as reported by the Central Bureau of Statistics in 2025. These conditions require a community empowerment strategy that can strengthen economic independence, particularly through optimizing local potentials in the digital era. This PKM aims to enhance the community’s capacity in utilizing digitalization for the development of Micro, Small, and Medium Enterprises (MSMEs), especially the village’s local product, cassava chips. The program’s methods included potential mapping, digital marketing education, product photography training, repackaging activities, and marketplace assistance, conducted over two days and involving 30 participants. The results indicate improvements in participants’ knowledge and skills related to digital marketing, product packaging, and online store management. Additionally, the program fostered increased entrepreneurial motivation and positive attitudes that support the economic independence of Karoya Village’s flagship products. The sustainability of this initiative is expected to be achieved through continued mentoring and collaboration among village authorities, the community, and higher education institutions.